Didactic strategy for the understanding of literary texts at the primary level - Moya Arnez, Juan José (2022)
The objective of the study was to enhance the understanding of literary texts in primary school students through the application of a didactic strategy, this implies the application of a strategy with ordered and sequential actions in a systemic way developed by the teacher and executed by the students of 5th and 6th year of the primary level in the area of Communication and Languages. Methodologically, the research was carried out from a dialectical perspective, with the application of theoretical methods such as dialectical, holistic holographic and modeling, empirically scientific observation. Instruments of survey, interview, diagnostic test and observation guides were used that allowed the systematization, analysis and explanation of the information obtained and it is concluded that the didactic strategy is a system of both theoretical and practical activities mediated by didactic actions, methods, means and forms of evaluation to a certain educational process.